The incidence of Consumer Law on financial crowdfunding - Díez Soto, Carlos Manuel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The development of financial crowdfunding raises, among other questions, the problem of determining how the rules on consumer protection should affect this area, not only with respect to investors (whose protection has been legally articulated on the basis of the instruments and categories of the financial market), but also with respect to those consumers who resort to this channel to finance projects of a non-business nature (with respect to which, in particular, the question of the applicability of the rules on consumer credit arises). All this, taking into account the peculiarities of crowdfunding as a financing system in which, together with project-owners and investors, the intermediary platform assumes a leading role. In this paper we analyze the response that Spanish and European legislators have been giving to the questions raised, giving rise, at the present time, to a situation of notable uncertainty.